When exhaustion meets permissiveness: a response surface analysis of parental burnout–parenting style interactions on childhood social anxiety - Yang, Peiyi; Yang, Lin; Liu, Xuerong; Feng, Zhengzhi (Frontiers in Pediatrics, 2025)
ObjectiveThis study examined the interactive effects of parental burnout and parenting styles (authoritative, authoritarian, and permissive) on childhood social anxiety using response surface analysis (RSA).MethodsThis cross-sectional study was conducted between November and December 2024 in primary schools in Chongqing, China. Participants (parents and their children) were required to complete online questionnaires, including the Parental Burnout Assessment (PBA), the Parenting Styles and Dimensions Questionnaire (PSDQ), and the Social Anxiety Scale for Children (SASC). RSA and polynomial regression models examined the non-linear interactions between parental burnout, parenting styles, and childhood social anxiety.ResultsA total of 724 datasets were included in the study. The findings indicated that significant congruence effects emerged for permissive parenting and parental burnout, and an inverted U-shaped curvature appeared along the line of incongruence with childhood social anxiety (curvature, a4 = −0.70, p = 0.009; slope a3 = −0.57, p = 0.272). Moreover, the curvature (a2 = −0.28, p = 0.089) and slope (a1 = 0.81, p = 0.068) were measured along the line of congruence, indicating that the line of congruence section curve is linearly rising.ConclusionThis study identifies a significant interactive effect between parental burnout and permissive parenting style on childhood social anxiety, highlighting the need for two-pronged interventions. Future research should investigate the longitudinal causal pathways between parental burnout–parenting style congruence and child social anxiety across diverse cultural contexts.